2022
DOI: 10.3389/fimmu.2022.945706
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunogenicity of an mRNA/LNP and a DNA vaccine targeting HIV gag conserved elements in macaques

Abstract: Immunogenicity of HIV-1 mRNA vaccine regimens was analyzed in a non-human primate animal model. Rhesus macaques immunized with mRNA in lipid nanoparticle (mRNA/LNP) formulation expressing HIV-1 Gag and Gag conserved regions (CE) as immunogens developed robust, durable antibody responses but low adaptive T-cell responses. Augmentation of the dose resulted in modest increases in vaccine-induced cellular immunity, with no difference in humoral responses. The gag mRNA/lipid nanoparticle (LNP) vaccine provided subo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 104 publications
0
16
0
Order By: Relevance
“…Interestingly, Valentin et al reported a strong antibody but not cellular immune response on immunized nonhuman primates when a specific ionizable lipid (property of Acuitas Therapeutics) was used to formulate p55Gag mRNA into LNPs before injection via the IM route. They observed that this Th2-biased polarization was promoted only at low dose of administrated mRNA [ 54 ]. These data suggest that the ionizable lipid-containing LNPs might have an intrinsic adjuvant effect with some evidence of a dose–response relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Valentin et al reported a strong antibody but not cellular immune response on immunized nonhuman primates when a specific ionizable lipid (property of Acuitas Therapeutics) was used to formulate p55Gag mRNA into LNPs before injection via the IM route. They observed that this Th2-biased polarization was promoted only at low dose of administrated mRNA [ 54 ]. These data suggest that the ionizable lipid-containing LNPs might have an intrinsic adjuvant effect with some evidence of a dose–response relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The surprising results of investigations into RNA immunogenicity for T cells speaks to the great importance of such vector choice for modulating both, the intensity and character of the response. Despite the power of RNA vaccines for inducing antibody responses, both a recent publication [22] and our unpublished work in nonhuman primates show that RNA priming can in many circumstances elicit comparatively poor T-cell responses. It is commonly observed that among groups of animals receiving serial mRNA vaccination, whether expressing intracellular or secreted antigens, impressive antibody responses testify to robust gene expression from the vaccine—while T-cell responses among PBMC remain anemic (<0.1%) or, in some animals, absent.…”
Section: Immunogens Targeting Alternative Viral T-cell Antigensmentioning
confidence: 83%
“…Further analysis in groups of HIV controllers and noncontrollers showed that several of these elements were indeed frequently targeted by HIV controllers, raising the possibility that CE vaccines could elicit similar responses across a wide range of HLA class I diversity [21]. Indeed, very recent data show the induction of strong responses in Non-Human Primates upon a DNA/RNA prime regimen, with the induction of both, CD4 and cytotoxic memory CD8 T cells [22,23]. A clinical trial testing this immunogen design in combination with a TLR9 agonist and bnAb treatments is ongoing.…”
Section: Therapeutic Vaccinesmentioning
confidence: 99%
“… Gómez et al (2021) used modified 1-methyl-3′-pseudouridylyl vectors that included a T-cell multiepitope construct encoding HIV-1 Gag, Pol, and Nef proteins conserved epitopes for protection against HIV-1 infection. Valentin et al (2022) found that LNP/mRNA vaccines expressing the HIV-1 Gag and Gag conserved region, when combined with Gag DNA vaccines, elicited strong humoral and cellular immune responses.…”
Section: Clinical Application Of Mrna Vaccines In Infectious Diseasesmentioning
confidence: 99%